Scalable Orbital Tuning of the 1,3-Diphosphacyclobutane-2,4-diyl Unit of Singlet Biradicaloid - Ueta, Yasuhiro; Ito, Shigekazu (Journal of organic chemistry, 2020)
The phosphino groups in 1,3-diphosphacyclobutane-2,4-diyl in the singlet biradicaloid play important roles in determining the physicochemical characteristics of the particular open-shell phosphorus heterocycles. Herein, we demonstrate that the introduction of para-substituted phenyl groups to the phosphorus atom induces useful photoabsorption and redox characteristics, as confirmed by the Hammett equation. These findings provided reliable methods for realizing desirable physicochemical properties of the open-shell singlet phosphorus heterocyclic chromophores based on programmed tuning of the molecular orbital energy levels of the particular open-shell singlet (non-Kekulé) heterocyclic unit. In addition, use of the thiophene substituent allowed confirmation of the orbital tuning by catenation of the P-heterocyclic units, with the >P–C4H2S–P< bridging component inducing splitting of the degenerate LUMO energy levels and destabilizing of the cationic species upon oxidation.